Compact and noncompact structures of a three-dimensional 3DKP(m, n) equation with nonlinear dispersion - İnç, Mustafa (Pergamon-Elsevier Science Ltd, 2013)
In this paper, we investigate exact-special solutions of the three-dimensional Kadomtsev-Petviashvili equation (3DKP(m, n)) with nonlinear dispersion. We use the ansatz method and the Exp-function method for this equation. So, we get general formulae for the compactons, solitary patterns, solitons and periodic solutions. In addition, we obtain a new travelling wave solution for the 3DKP(2, 1) equation by the Exp-function method. Published by Elsevier Ltd
Keywords: Compacton; Solitary pattern; Travelling wave solutions; KP equation; The ansatz and the Exp-function method